Recovery and adaptation from repeated intermittent-sprint exercise - Leeder, J. D. C.; van Someren, K. A.; Gaze, D.; Jewell, A.; Deshmukh, N. I. K.; Shah, I.; Barker, J.; Howatson, G. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This investigation aimed to ascertain a detailed physiological profile of recovery from intermittentsprint exercise of athletes familiar with the exercise and to investigate if athletes receive a protective effect on markers of exercise-induced muscle damage (EIMD), inflammation, and oxidative stress after a repeated exposure to an identical bout of intermittent-sprint exercise. Methods: Eight well-trained male team-sport athletes of National League or English University Premier Division standard (mean ± SD age 23 ± 3 y, VO2max 54.8 ± 4.6 mL/kg·min) completed the Loughborough Intermittent Shuttle Test (LIST) on 2 occasions, separated by 14 d. Maximal isometric voluntary contraction (MIVC), countermovement jump (CMJ), creatine kinase (CK), C-reactive protein (CRP), interleukin-6 (IL-6), F2-isoprostanes, and muscle soreness (DOMS) were measured before and up to 72 h after the initial and repeated LISTs. Results: MIVC, CMJ, CK, IL-6, and DOMS all showed main effects for time (P < .05) after the LIST, indicating that EIMD was present. DOMS peaked at 24 h after LIST 1 (110 ± 53 mm), was attenuated after LIST 2 (56 ± 39 mm), and was the only dependent variable to demonstrate a reduction in the second bout (P = .008). All other markers indicated that EIMD did not differ between bouts. Conclusion: Well-trained games players experienced EIMD after exposure to both exercise tests, despite being accustomed to the exercise type. This suggests that well-trained athletes receive a very limited protective effect from the first bout.